Assessment of Prevalence and Awareness Regarding Thyroid Disorders Among Nursing Students in a Selected Nursing College, Lucknow - Ms.NanditaTripathi; Ms. Akshita Saxena; Ms. Khushi Singh; Ms. Lekhani Nigam; Ms. Roli Verma; Ms. Shailja Yadav; Ms. Upanshi Banswar (Young Nurses Journal of Research, 2026)
Introduction: Despite their high prevalence, thyroid disorders often remain underdiagnosed, especially in subclinical stages, which may progress to overt disease if left untreated. Undiagnosed thyroid dysfunction can lead to complications including cardiovascular disorders, menstrual irregularities, infertility, cognitive impairment, mood disturbances, and reduced quality of life. Iodine deficiency remains a major preventable cause of thyroid disorders worldwide, particularly in regions with low dietary iodine intake. Nursing students represent a crucial population group, as they are future healthcare providers responsible for early detection, health promotion, and patient education. Thyroid dysfunction among nursing students may negatively impact academic performance, concentration, memory, and overall well-being, potentially affecting their professional development. Assessing both the prevalence of thyroid disorders and the level of awareness among nursing students is therefore essential. Aim of this study is to assess the prevalence of thyroid disorders and the level of awareness regarding thyroid disorders among nursing students in selected nursing colleges of Lucknow. Materials and Methods: This study employed a descriptive, non-experimental cross-sectional design to assess the prevalence and awareness regarding thyroid disorders among nursing students. The study was conducted at St. Mary’s College of Nursing, Lucknow, Uttar Pradesh, India. The study population comprised nursing students aged 17–25 years. The accessible population included students enrolled at St. Mary’s College of Nursing. A total of 263 participants were selected using a convenience sampling technique. Eligible participants included students enrolled in B.Sc Nursing, GNM, ANM and paramedical courses who were available during the data collection period and provided informed consent. Students. Screening camp was organized to assess thyroid status. Results: Thyroid screening results revealed that 228 (86.7%) students had normal TSH levels, while 25 (9.5%) exhibited hypothyroidism and 10 (3.8%) had hyperthyroidism. Hypothyroidism was more common than hyperthyroidism among the participants. Pertaining to level of knowledge on thyroid disorders among nursing students mean score of approximately 28.3 indicates that, on average, nursing students fall within the moderate knowledge category, but are close to the threshold of adequate knowledge. The standard deviation of 8.5 shows a moderate level of variation in knowledge scores. This means that while many students have good knowledge, a noticeable proportion still have low understanding. This variation is also reflected in the distribution, where 14.1% of students have inadequate knowledge, compared to 49.0% with adequate knowledge. Conclusion: In conclusion, this study highlights that thyroid disorders are not uncommon among nursing students, with 13.3% showing abnormal TSH levels. Hypothyroidism was found to be more prevalent than hyperthyroidism, indicating a noticeable burden of thyroid dysfunction even in a young and otherwise healthy population. This raises concern as such conditions may affect both the well-being and academic performance of students. The findings also show that while many students have moderate to adequate knowledge about thyroid disorders, a considerable number still lack sufficient understanding. This gap in knowledge suggests the need for stronger educational efforts within the nursing curriculum. Improving awareness through targeted teaching, workshops, and regular health education programs can help students better recognize early symptoms and seek timely care.